2022
DOI: 10.1186/s40168-022-01367-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring AI-2-mediated interspecies communications within rumen microbial communities

Abstract: Background The rumen is an ecosystem with a complex microbial microflora in which microbes initiate biofilm formation by attaching to plant surfaces for plant degradation and are capable of converting feed to nutrients and energy via microbial processes. Quorum sensing (QS) is a cell-to-cell communication mechanism that allows microbes to synchronize the expression of multiple genes in the group to perform social behaviors such as chemotaxis and biofilm formation using self-synthesized QS signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Generally, microbes communicate with each other via diverse QS signals that act as microbial languages [48,49], such as acyl-homoserine lactones (AHLs), indole, autoinducing peptides (AIPs), 4hydroxy-2-alkylquinolines (HAQs), and autoinducer-2 (AI-2), to realize similar functions like bio lm development and virulence [32,50]. In a previous study, we had constructed a comprehensive database (QSHGM) and the corresponding undirected QS communication network (QSCN) for human gut microbes for the rst time [51].…”
Section: Data Analysis Of the Qscn Of Several Human Gut Microbiotamentioning
confidence: 99%
“…Generally, microbes communicate with each other via diverse QS signals that act as microbial languages [48,49], such as acyl-homoserine lactones (AHLs), indole, autoinducing peptides (AIPs), 4hydroxy-2-alkylquinolines (HAQs), and autoinducer-2 (AI-2), to realize similar functions like bio lm development and virulence [32,50]. In a previous study, we had constructed a comprehensive database (QSHGM) and the corresponding undirected QS communication network (QSCN) for human gut microbes for the rst time [51].…”
Section: Data Analysis Of the Qscn Of Several Human Gut Microbiotamentioning
confidence: 99%
“…The variability of results in the above-mentioned experi ments highlights the need to employ both culture-dependent and culture-independent methods for investigating QS in the rumen. Indeed, numerous studies have now utilised genomic, metagenomic, or metatranscriptomic analysis, revealing a large diversity of potential QS mechanisms within the rumen [ 6 , 23 , 24 ]. For example, the advent of the Hungate collection, which sequenced 410 rumen bacteria and 21 archaea isolate cultures, allowed the mining of these genomes against known QS genes [ 23 , 32 ].…”
Section: Quorum Sensing In the Rumenmentioning
confidence: 99%
“…Interestingly, this Citrobacter species genome also contained luxS and luxR genes representing the potential to engage in multiple QS systems, i.e., both AHL and AI-2 [ 23 ]. Liu et al [ 24 ] expanded this mining of rumen genomes to include 948 bacterial genomes and 33 archaeal genomes, sourced from Shi et al [ 33 ], Gharechahi et al [ 34 ], and GenBank [ 35 ]. In this study they found more extensive evidence of AHL QS, with 5 archaeal genomes (all from the genus Methanobrevibacter ) and 58 bacterial genomes containing AHL genes, mainly harboured by the following orders; Eubacteriales, Bacteroidia, Clostridiales, and Selenomonadales [ 24 ].…”
Section: Quorum Sensing In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminant's rumen houses dense and complex community of symbiotic microbes that work together to break down lignocellulose [6]. These rumen microbial communities are perceived as the most potential biochemical reservoir of inordinately diverse and multi-functional cellulolytic enzymes with peculiar functional adaptation to enhance green biotechnological processes [7]. Bacterial community dominates the ruminal environment and hence considered as the most efficient biomass degrading enzymes in the herbivore gut microbiome.…”
Section: Introductionmentioning
confidence: 99%